Precision nutrient and irrigation management influences the growth, rhizosphere characters and yield of soybean (Glycine max) under system of crop intensification - SACHIN, K S; DASS, ANCHAL; DHAR, SHIVA; RAJANNA, G A; SINGH, TEEKAM; SUDHISHRI, S; KUSHWAHA, H L; KHANNA, MANOJ (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted during rainy (kharif) seasons of 2020 and 2021 at research farm of ICAR-IARI, New Delhi to study the effect of precision nutrient and irrigation management on growth and productivity of soybean [Glycine max (L.) Merr.] under system of crop intensification (SCI). The study was carried out in a split-plot design and replicated thrice. The main-plot included 3 irrigation practices, I1, [standard flood irrigation at 50% DASM (FI)] and sprinkler (Spr); I2 (Spr 80% ETc); I3 (Spr 60% ETc) and sub-plots having 5 precision nutrient management (PNM) practices, viz. PNM1 [SCI protocol]; PNM2 [RDF, Basal dose incorporated (50% N, full dose of P and K)]; PNM3 [RDF, Basal dose point placement (BDP) (50% N, full dose of P and K)]; PNM4 [75% RDF, BDP (50% N, full dose of P & K)] and PNM5 [50% RDF, BDP (50% N, full P and K)] and 1 absolute control with conventional practice. Further, for PNM2-PNM5 remaining 50% N was supplied through SPAD assisted top-dressing. PNM and irrigation practices improved the plant height and number of branches of soybean. Spr 80% ETc recorded significantly higher crop growth indices, viz. CGR (9.13 g/m2/day), RGR (31.48 mg/g/day), NAR (16.47 mg/cm2/day) and LAI (2.02 cm2/plant) over FI at 60–90 DAS. Root attributes also improved under SCI over control. The mean grain yield was significantly higher in Spr 80% ETc (2.50 tonnes/ha) over FI. Similarly, PNM3 recorded significantly higher mean grain yield (2.44 tonnes/ha) over PNM5. Overall, precision nutrition and irrigation enhanced the soybean growth and yield under SCI, hence could be propounded in the soybean growing regions.